Effect of Fe components in red mud on catalytic pyrolysis of low rank coal. (February 2022) - Wang, Yiming; Li, Yang; Wang, Guijin; Wu, Yunfei; Yang, He; Jin, Lijun; Hu, Song; Hu, Haoquan
Abstract: Bayer red mud (RM) is a solid waste in alumina production, and the main components is Fe2 O3 . To investigate the effect of Fe2 O3 in RM on pyrolysis of low-rank coal and catalytic upgrading mechanism on tar quality, pyrolysis experiments of pure Fe2 O3 and RM mixed with a lignite, Baiyinhua (BYH) coal, were carried out. The results indicate that RM exhibits a similar catalytic effect to Fe2 O3 in terms of product distribution and tar composition of coal pyrolysis. At 20% addition of RM or Fe2 O3 in coal, the yield of gas and water increases, while that of char decreases; the yield of H2 increases by 38.6% or 37.1%, and the yields of CO and CO2 increase by 58.9%, 78.1% and 24.6%, 44.1%, respectively. GC and GC-MS results prove that the existence of RM or Fe2 O3 improve the tar quality, and RM shows a better effect, as the content of heavy components decreases by 11.7% with RM and 5.1% with Fe2 O3 . Besides, the content of bisphenol, aliphatic hydrocarbon, oxygenated compounds and heteroatomic compounds decrease simultaneously, thus generating more monophenol and naphthalene. Several characterizations show that Fe2 O3, as an active component of RM, provides lattice oxygen species to participate in the reaction and changes to Fe3 O4 by partial oxidation during the pyrolysis process. TGA results and kinetic analysis of coal pyrolysis illustrate that RM can promote BYH coal pyrolysis and increase the yield of gas and liquid. Graphical abstract: Image 1 Highlights: The role of Fe2 O3 in red mud (RM) on Baiyinhua coal catalytic pyrolysis is revealed. RM exhibits better effect on product distribution and tar quality than pure Fe2 O3 . Fe2 O3 in RM provides lattice oxygen species to participate in the reaction. TG and kinetic results further prove the promotional effect of RM and Fe2 O3 .